Financial Feasibility and Strategic Benefit Assessment of the Coal Hauling Road and Jetty Project in Muara Pahu (Case Study: Bangun Group, Kalimantan, Indonesia) - Eddy Karlowee; Gallang Perdhana Dalimunthe; Widhyawan Prawiraatmadja (Eduvest - Journal of Universal Studies, 2026)
Coal remains a significant energy source in global and regional economies, particularly in developing countries where reliable energy supply and industrial growth continue to depend on coal availability. However, increasing production capacity requires reliable logistics infrastructure to overcome transportation constraints and operational risks. The Bangun Group’s Tabang Project in East Kalimantan has experienced challenges related to seasonal disruptions in river transportation, which may affect coal delivery continuity and future production expansion. This study aimed to evaluate the financial feasibility and strategic benefits of the Muara Pahu Coal Hauling Road (CHR) and jetty project as a long-term logistics infrastructure investment. A quantitative case study approach was applied using capital budgeting and cost–benefit analysis methods. The assessment utilized secondary data from company reports, project documentation, industry references, and financial assumptions, with evaluation indicators including Net Present Value (NPV), Internal Rate of Return (IRR), Return on Investment (ROI), Payback Period, Benefit–Cost Ratio (BCR), and sensitivity analysis. The results showed that the project generated substantial economic value, with a positive NPV, an IRR exceeding the required rate of return, and a BCR of 3.18, indicating that the project benefits significantly exceeded the investment costs. Sensitivity analysis confirmed the project’s resilience under variations in transportation volume, tariffs, operating costs, and discount rates. Beyond financial performance, the project improved logistics reliability, reduced transportation disruption risks, supported production scalability, and strengthened strategic infrastructure control.